2012
DOI: 10.1111/j.1600-051x.2012.01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipids modify periodontal infection ‐ C‐reactive protein association

Abstract: This study suggests that the relation of periodontal infection to the systemic inflammatory condition is more complicated than previously presumed. The findings of this study suggest that the possible systemic effect of periodontal infection is dependent on serum lipid composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
6
4
0
Order By: Relevance
“…This corresponds to and confirms our earlier findings on the role of HDL and LDL in the association between the number of teeth with deepened periodontal pockets and CRP levels (Haro et al. ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This corresponds to and confirms our earlier findings on the role of HDL and LDL in the association between the number of teeth with deepened periodontal pockets and CRP levels (Haro et al. ).…”
Section: Discussionsupporting
confidence: 93%
“…Regarding IL-6, the findings are in line with the results of a number of non-experimental and experimental studies where periodontitis and ligatureinduced periodontitis were reported to be associated with systemic inflammation. It should be noted that this finding is by no means unexpected, because IL-6 is known to trigger off CRP secretion in the liver and we have earlier reported a positive association between the number of teeth with deepened periodontal pockets and the CRP level of subjects using the same Health 2000 data (Haro et al 2012). In the stratified analyses, we observed that a systemic inflammatory response was somewhat stronger among those with an unfavourable lipid profile (i.e.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations